Variabilidade espacial de atributos do solo que influenciam a produção de arroz vermelho no Vale do Apodi - RN - Barreto, Herlon Bruno Ferreira (2012)
Irrigated red rice has been cultivated for decades in Apodi Valley, Brazil, where it is a cash crop and main economic resource for many small farm families. However, in other regions of Brazil red rice is little known and little cultivated. This study had as objective to assess spatial variability of soil attributes that influence irrigated red rice production in Apodi Valley, and characterize spatial dependence of those attributes and also of rice yield. The work was carried out in two farms of the county of Apodi, RN, Brazil, in a lowland region where is established the Apodi Valley Association of Red Rice Growers. Each farm had a production area divided in fifteen subareas, from which were determined soil chemical and physical-hydric characteristics. Samples were taken at 0 - 15 and 15 30 cm depths, according to a grid with regular spacing of 20 x 20 m in Area 1 and 10 x 10 m in Area 2. Sampling spots were georeferenced according to Cartesian coordinates that allowed the use of geostatistics in the study of spatial variability. Physical-hydric determinations included soil texture, permanent wilting point, field capacity, soil density, particle density and available water content. Soil chemical determinations included organic matter content and contents of Ca2+, Mg2+, K+, Na+, P, Cu2+, Mn2+, Fe2+ and Zn2+. Rice yield components determined were panicle number per area, mass of hundred grains and yield. Descriptive statistics was used for analyzing data general behavior and to identify outliers. Spearman correlation and multiple linear regression analysis were used for identifying probable causes of variability. Mean yields obtained were 7527 kg ha-1 and 3832 kg ha-1, in areas 1 e 2, respectively. Soil physical-hydric variables correlated to production components were: available water content, permanent wilting point, soil density and contents of clay and silt. Soil chemical variables correlated to rice yield components were: calcium, magnesium, phosphorus, sodium, potassium, zinc, copper, manganese, iron and organic matter